KISSING NEVUS RECONSTRUCTION WITH A SUPRACLAVICULAR GRAFT: A RARE CASE REPORT: Poster Presentation - Case Report - Resident - Lissa Novia Permatasari; Ratna Doemilah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Kissing nevus is a rare form of congenital nevus that occurs on upper and lower eyelid of one eye, forming a large nevus when the eyelids are closed. This condition causes functional and aesthetic problems thus the reconstruction is essential. Case Illustration : A 23-years old female presented to our ophthalmology outpatient clinic with complain of having painless, black colored, non-progressive nevus over left upper and lower eyelids since birth that cosmetically unpleasing. The dark brown-black colored was sized 55x30 mm with hypertrichosis covering approximately two third of both left upper and lower eyelid margins and extending to cheek. The entire nevus was excised and reconstructed by supraclavicular full thickness skin graft, lateral canthopexy and canthoplasty. Three weeks after operation showed satisfactory results. Histological examination revealed intradermal nevus pigmentosus. Discussion : The reconstruction of eyelid after excision remains a challenge because of its specialized function and cosmetic significance. Ideally, the reconstruction should provide a stable eyelid margin, protect the ocular surface, and sustain mobility. Free skin grafts harvested from the control lateral eyelid, postauricular, supraclavicular, and upper arm region have been the most common reconstructive approach. The supraclavicular area is a reliable donor option to cover large head and neck defects due to its similarity in colour, thickness, and flexibility. Conclusion : Free supraclavicular graft is safe, reliable and cosmetically acceptable choice for reconstruction head and neck defects.